2020
DOI: 10.1002/aocs.12345
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Fat Bloom in Chocolate Model Systems: Replacement of Cocoa Powder with Sugar Particles and the Effects of Lecithin

Abstract: To investigate the effects of particulates on fat bloom in chocolate, model systems were formulated with 50% nonfat particles and 50% cocoa butter on a mass basis, where cocoa powder was gradually replaced by sugar particles (sucrose, maltitol, corn syrup solids [CSS], and polydextrose [PD]). Bloom extents were investigated in three ways: the change in whiteness index (ΔWI), white area percentage, and visual bloom level. All three bloom evaluation methods showed similar trends, although the methods were more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In case an amount of 0.5% or 1% seed powder was used for seeding, initial chocolate hardness was approx. 10 N, with the highest values again for samples with nougat #D. In the first 20–30 d of storage, the systems slightly solidified, presumably because of an ongoing slow crystallization of cocoa butter and a resulting formation of a fat crystal network in the bottom nougat layer that presumably blocks the fat migration pathway due to microstructural changes [ 27 , 28 ]. At this particular time, chocolate hardness was almost similar to the hardness of chocolate on top of the industrially tempered control nougat.…”
Section: Resultsmentioning
confidence: 99%
“…In case an amount of 0.5% or 1% seed powder was used for seeding, initial chocolate hardness was approx. 10 N, with the highest values again for samples with nougat #D. In the first 20–30 d of storage, the systems slightly solidified, presumably because of an ongoing slow crystallization of cocoa butter and a resulting formation of a fat crystal network in the bottom nougat layer that presumably blocks the fat migration pathway due to microstructural changes [ 27 , 28 ]. At this particular time, chocolate hardness was almost similar to the hardness of chocolate on top of the industrially tempered control nougat.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the diverse shapes and properties of sugar particles lead to varying effects on the formation of chocolate bloom. During storage, fat bloom was encouraged by sucrose, whereas chocolate systems containing maltitol, corn-syrup solids, and polydextrose parti-cles did not display notable bloom [113]. In addition, the presence of sugar crystals restrains the impact of emulsifiers on the crystallization of cocoa butter and retards its transition from the IV form to the V form [100].…”
Section: Effect Of Organic Additivesmentioning
confidence: 99%
“…Although the TAGs composition of fats systems is of great relevance regarding final products appearance and texture, the nonfat components of the matrix of a product may also play a key role in chocolate and confections. It was reported that nucleation rate and polymorphic transition to higher‐stability polymorphs in cocoa butter contained in cocoa powder was faster than in bulk (Palmieri & Hartel, 2019) and that bloom extent strongly depends on sugar type and other additives such as lecithin (Jin & Hartel, 2020). According to Palmieri and Hartel (2019), crystallization in cocoa products was strongly influenced by both the intrinsic attributes of the cocoa powder and the conditions of the tempering process.…”
Section: Chemical Composition Of Fat Systemsmentioning
confidence: 99%